Evaluation of the relationship between human brucellosis and pregnancy loss (Annals of Medical Research, 2021)
Aim: Brucellosis is a zoonotic infection caused by bacteria of the genus Brucella. The disease causes genitourinary systeminvolvement and abortion, which is the most critical complication of the disease, in cattle. Although it is known to cause spontaneousabortion, preterm birth and intrauterine death in humans, the number of systematic studies on the subject is limited. This studycompared the patients who experienced pregnancy loss and women who carried their pregnancy to term without any problems interms of serology for brucellosis in our region which is an endemic region.Materials and Methods: The study was conducted in the Clinic of the Department of Obstetrics and Gynecology in GaziantepUniversity Hospital between August 2012-June 2013. The study was conducted with 71 patients who experienced intrauterinepregnancy loss and 109 women who carried their pregnancy to term without any problems as the control group, wherein all subjectswere aged between 18 and 40. These two groups were in a similar age group and had a similar gestational age.Results: There were 4 (5,6%) subjects who were brucella-positive in the patient group and 1 (0,9%) subjects who were brucella-positive in the control group according to the serology for brucellosis. C-reactive protein, erythrocyte sedimentation rate, aspartateaminotransferase, abortus, and parity were significantly high in women who experienced pregnancy loss (p